Truncation of a β-barrel scaffold dissociates intrinsic stability from its propensity to aggregation - Curto, Lucrecia María (2012)
Δ98Δ is a functional all-β sheet variant of intestinal fatty acid binding protein (IFABP) that was generated by controlled proteolysis. This framework is useful to study the molecular determinants related to aggregation of β-barrel proteins. Albeit displaying increased conformational plasticity, Δ98Δ exhibits a nativelike β-barrel topology and is able to support a cooperative folding behavior. Here we present a comparative study of IFABP and Δ98Δ regarding their conformational perturbation and aggregation propensity triggered by trifluoroethanol. Both proteins share a common nucleation-elongation mechanism, whereby the rate-limiting step is the formation of stable dimeric nuclei followed by the association of monomers to the growing aggregates. Despite leading to a less stable structure, the extensive truncation of IFABP yields a form exhibiting a somewhat lower tendency to aggregate. This finding appears at odds with the established notion that a perturbation of the native compact fold should necessarily favor the population of aggregation-prone species. In addition to the aggregation propensity dictated by a given amino-acid sequence, our contention holds that long-range interactions might also play a major role in determining the overall aggregation propensity. © 2012 Biophysical Society.